2001
DOI: 10.1128/jvi.75.14.6482-6491.2001
|View full text |Cite
|
Sign up to set email alerts
|

CpG Oligodeoxynucleotides with Hepatitis B Surface Antigen (HBsAg) for Vaccination in HBsAg-Transgenic Mice

Abstract: DNA motifs containing unmethylated CpG dinucleotides within the context of certain flanking sequences enhance both innate and antigen-specific immune responses, due in part to the enhanced production of Th1-type cytokines. Here we explored the ability of CpG-containing oligodeoxynucleotides combined with recombinant hepatitis B surface antigen (HBsAg) to induce Th1 responses in mice that are transgenic for this antigen and that represent a model for asymptomatic hepatitis B virus chronic carriers. This was com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…In previous studies, several vaccination strategies attempted to break systemic HBV tolerance in an HBV-tg mouse model (8,14,30,31); however, because HBV DNA integrates into the genome of mouse embryos in this model, their immune systems become nonresponsive (i.e., tolerant) to HBV because of central clonal deletion of HBV-specific T and B cells, which does not reflect the acquired tolerant state in most human CHB patients. Because HBV is unable to infect new hepatocytes in our HBVcarrier mouse model, no immunopathology or innate immune signals can occur, and low HBV titers are observed in HBV-carrier mice; these aspects of the model more closely resemble human asymptomatic chronic HBV carriers, who usually do not require treatment, than CHB patients (2,3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, several vaccination strategies attempted to break systemic HBV tolerance in an HBV-tg mouse model (8,14,30,31); however, because HBV DNA integrates into the genome of mouse embryos in this model, their immune systems become nonresponsive (i.e., tolerant) to HBV because of central clonal deletion of HBV-specific T and B cells, which does not reflect the acquired tolerant state in most human CHB patients. Because HBV is unable to infect new hepatocytes in our HBVcarrier mouse model, no immunopathology or innate immune signals can occur, and low HBV titers are observed in HBV-carrier mice; these aspects of the model more closely resemble human asymptomatic chronic HBV carriers, who usually do not require treatment, than CHB patients (2,3).…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, combining HBsAg vaccine with an immunostimulator, such as CpG, exhibited improved efficacy to break HBV tolerance via Th1-biased mechanisms (14). On the other hand, combining HBsAg vaccine with an antiviral agent, including lamivudine, was favored in other trials, because HBV-specific T cell hyporesponsiveness during CHB infection always correlated with high viral load (15).…”
mentioning
confidence: 99%
“…Furthermore, adoptive transfer of splenocytes from immunized to naïve mice conferred protection against vvHCV.S challenge and the selective depletion of the CD4 ϩ or CD8 ϩ population abolished the protective immunity (25), suggesting that CD4 ϩ and CD8 ϩ may be important for this immunity. Adjuvants have been used with conventional vaccines to elicit an early, robust, and durable immune response, and they can modulate the immune response toward different T-helper response (Th1 versus Th2) (1,5,8,14,17,23,38,40). Vaccination of HCV-LP combined with adjuvant(s), ASO1B (monophosphoryl lipid A and QS21), and/or CpG 10105 (oligonucleotides containing the immunostimulatory CpG motif) enhanced HCV-specific antibody production and promoted cellular immune responses with a Th1 bias in AAD mice (30).…”
mentioning
confidence: 99%
“…Immunization of transgenic animals with HBsAg vaccine supplemented with CpG DNA led to clearance of serum HBsAg and the development of anti-HBs, with concurrent down-regulation of HBV mRNA production in the liver. Adoptive transfer experiments of T cells from such animals showed that they were able to partially control transgene expression in the liver and to clear HBsAg without an antibody requirement [92] . A CpGcontaining HBsAg vaccine was shown to overcome hyporesponsiveness normally seen in immunized orangutans [93] .…”
Section: Viral Specific T Cell Responsesmentioning
confidence: 99%
“…Another adjuvant of potential benefit is CpG DNA, a synthetic oligonucleotide that preferentially stimulates Th1 responses, with the production of IL12 and IFNg [92] . Immunization of transgenic animals with HBsAg vaccine supplemented with CpG DNA led to clearance of serum HBsAg and the development of anti-HBs, with concurrent down-regulation of HBV mRNA production in the liver.…”
Section: Viral Specific T Cell Responsesmentioning
confidence: 99%